Learning Material Development Based on Wetland Environment to Improve Student’s Industrial Revolution 4.0 Skills and Multiple Intelligence - Noorhapizah, Noorhapizah; Pratiwi, Diani Ayu; Azzahra, Dina Rizky; Sepriyani, Ika (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The problem with this study is the unavailability of teaching materials which is containing high order thinking skills and multiple intelligence improvement based on local wisdom. While the development of high order thinking skills and multiple intelligence becomes one of the great goals that are expected to get a productive future generation. The purpose of this study are (1) Produce the innovative textbook which is containing high order thinking skills and multiple intelligence, (2) this study want to know effectiveness of learning materials based on local wisdom to improve high order thinking skills and multiple intelligence. This study use research and development methods that will develop products in the form of teaching materials and textbooks containing high order thinking skills and multiple intelligence improvement based on local wisdom. The research design refers to the Borg & Gall design which consists of 10 steps. The result mentioned that thematic textbooks containing high order thinking skills and multiple intelligence based on local wisdom deserve to be used, have effectiveness for the fifth grade of elementary school based on evaluation from the material draft expert, media expert, language expert and field test. Based on the results, it can be concluded that there is a significant difference between the results of the experimental class post test and the control class post test scores.